Minimum Quality Standards in Hedonic Markets with Environmental Externalities - Giulio Ecchia; Luca Lambertini; Alessandro Tampieri (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
We investigate the introduction of a minimum quality standard (MQS) in a vertically differentiated duopoly with an environmental externality. We establish that the MQS bites only if the hedonic component of consumer preferences is sufficiently strong. Then, we illustrate an underlying tradeoff between the beneficial effects of quality enhancement on prices and the associated undesirable increase in the environmental externality.
Keywords: L13; L51; Q50; 330